211k views
1 vote
Solve the following equation for q. 8q + 4p + 4 = 4q – 8.

a. q = -p - 3
b. q = -2p + 3
c. q = -2p - 3
d. q = -p + 3

User FylmTM
by
4.4k points

1 Answer

2 votes

Answer:

a. q= -p - 3

Explanation:

8q+ 4p + 4= 4q - 8

8q (- 8q) + 4p + 4 = 4q (-8q) -8

4p +4 = -4q -8

4p + 4 (+8) = -4q -8 (+8)

4p + 12 = -4q

(4p + 12)/-4 = (-4q)/-4

-p -3 = q

User Johnny Willemsen
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.